Acute gastric necrosis due to ingestion of hydrochloric acid - Mañana, Julio; Zito, Eduardo; Llard, Washington; Pereira, César; Kalechsztajn, Jaime (Cirugía del Uruguay, 2021)
The paper refers to a case of acute gastric necrosis due to the ingestion of hydrochloric acid. There is an acute stage dominated by collapse, respiratory' insufficiency, acidosis and faringo-esophago-gastric burns; a subacute stage of gastric necrosis with perforation and peritonitis. At this stage we performed an atypical segmentary gastrectomy, and we made a gastric · tube. The treatment was ,completed by a degravitational gastrostomy and a transgástric duodenostomy for feeding. There was an intermediate stage characterized by digestive fistulas, digestive hemorraghes and a deep metabolic perturbation. Our patient is still in this stage, which may last for many years, and in which there is always the danger of a cicatrical stenosis; should this happen, we would have to resort to a plastic procedure.